Cervical HPV infection and related diseases among 149,559 women in Fujian: an epidemiological study from 2018 to 2023 - Lin, Kun; Hong, Qiyang; Fu, Ya; Tu, Haijian; Lin, Hua; Huang, Jiexiang; Hu, Yajing; Huang, Minjun; Chen, Mingqiao (Frontiers in Microbiology, 2024)
To comprehensively analyze the epidemiological features of human papillomavirus (HPV) and HPV-related cervical diseases in females aged 35-64 years.Methods A total of 149,559 samples of exfoliated cervical cells screened for HPV and related cervical lesions from January 2018 to December 2023 were enrolled. The prevalence of 15 high-risk and 6 low-risk HPV genotypes were detected, and the cervical cytology were analyzed. The impact of single and multiple HPV infections was characterized, and the effect of age was studied. Results The cervix cytology was normal in 86.60% of the females, while 7.13% of the females were diagnosed with cervix inflammation, 0.60% with ASC-US, 0.22% with ASC-H, 0.72% with LSIL, 0.49% with HSIL, 0.03% with ICC. The highest median age was observed in ASC-H group with 54 years old. Females with primary school education or lower have the highest positive rates. The overall HPV prevalence was 8.60%. The relatively prevalent HPV types were HPV52, 58, 16, 39, 51. HPV16, HPV18, HPV58, HPV33 and HPV52 were the top5 predominant types in ICC patients. 17.41% females suffered from multiple HPV infection with the most frequently co-infection subtypes being HPV52, HPV58 and HPV16. The prevalence of all HPV subtypes increased with age. Multiple HPV infections accounted for a larger proportion in those aged above 55 years. The peak HPV16 prevalence was observed in ICC group in cases aged 45-49 and 55-59. The peak HPV33 prevalence was observed in younger individuals aged 40-44 who developed ICC. Conclusions More action should be taken against HPV33 infection.